The Imagination in Hume's Philosophy : the Canvas of the Mind. - Costelloe, Timothy M. (Edinburgh studies in Scottish philosophy., 2017)
The prominence of the imagination in David Hume's philosophy has been recognised by generations of readers. In this rich study, Timothy Costelloe gives us the most complete picture yet of Hume's view of imagination - and its place in his philosophy.